Investigating association of predisposition genes as a risk of developing multifactorial diseases - Arginbekova, Assel (2023)
This thesis explores directions that explain the genetic mechanisms of predisposition to multifactorial diseases. In this regard, two common and severe diseases, periodontitis and pancreatic diseases, belonging to the group of multifactorial diseases, were studied. Our study demonstrated an association between clinical status and copy number variation and single nucleotide polymorphisms in the two diseases. The first project aimed at determining the association of the AMY gene with pancreatic diseases. It should be noted that there have been no previous studies to investigate the association between the AMY copy number variants and pancreatic diseases, which prompted the search for this association. Research on AMY copy number variants has mainly been in the area of population differences and obesity. It is assumed that copy numbers of the AMY gene are associated with the occurrence of multifactorial diseases. Multiple pancreas diseases, such as acute and chronic pancreatitis or cancer, can be considered multifactorial diseases. Therefore, for the first time in the project, the copy number variants of the AMY1, AMY2A and AMY2B genes and the role of the genes in the development of diseases associated with the pancreas have been investigated. We have studied the possible role of the CNV amylase gene by laboratory testing of biological material (blood) from Queen's Medical Centre patients. The study found evidence of a positive association between the amylase gene and pancreatic diseases. And also, the clinical and genetic features of various forms of pancreatitis were studied. The range of copy numbers of the AMY gene was determined specifically for each form of pancreatic disease. In addition, the influence of individual factors (age, gender and BMI) on developing the risk of pancreatic diseases was studied. Clinical and genetic features of various forms of pancreatitis were also investigated. The presence of N34S mutations in the SPINK1 gene was determined in the development and progression of pancreatitis. The frequency of occurrence of the N34S mutation in the SPINK1 gene was identified among patients with pancreatic diseases in Nottingham, UK. A comparative analysis of the frequency of occurrence in other populations was also carried out. A positive association between N34S mutation and pancreatic disease was identified. The second periodontal disease project focused on the relationship between clinical factors and the presence of SNPs and flanking α-defensin genes. The study identified the association between the periodontitis phenotype and the DEFA gene. Previously, combinations of clinical signs of periodontitis and the DEFA gene have not been sufficiently studied. Therefore, the research was expanded to investigate the relationship between the main clinical symptoms of periodontitis with specific polymorphisms of the DEFA gene, which is responsible for the immune response and the body's defences. The study identified eight specific SNPs associated with periodontitis's four most important clinical characteristics. In the thesis, the first attempt was made to determine the associations of the AMY1, AMY2A and AMY2B genes with the development of diseases and the formation of clinical forms. Certain polymorphisms of the DEFA gene have been established as associated with the disease, taking into account clinical features.